Cell biology of chromerids: autotrophic relatives to apicomplexan parasites - Oborník, Miroslav; Lukeš, Julius (International review of cell and molecular biology, 2013)
Chromerida are algae possessing a complex plastid surrounded by four membranes. Although isolated originally from stony corals in Australia, they seem to be globally distributed. According to their molecular phylogeny, morphology, ultrastructure, structure of organellar genomes, and noncanonical pathway for tetrapyrrole synthesis, these algae are thought to be the closest known phototrophic relatives to apicomplexan parasites. Here, we summarize the current knowledge of cell biology and evolution of this novel group of algae, which contains only two formally described species, but is apparently highly diverse and virtually ubiquitous in marine environments.
Keywords: zvířata; Animals; Humans; Apicoplasts; Apicomplexa; apikoplasty; lidé; biologie buňky; Cell Biology